Hubungan antara Frekuensi Bangkitan Epileptik dengan Kualitas Hidup Pasien Epilepsi di RSUD Mangusada Tahun 2021-2022 - I Gusti Ngurah Agung Cahyadi Putra; Saktivi Harkitasari; Komang Triyani Kartinawati (Aesculapius Medical Journal, 2022)
Epilepsy is an abnormal condition in the brain characterized by the continuous emergence of predisposing factors in the occurrence of an epileptic seizure, which is also characterized by the presence of neurobiological, cognitive, psychological, and social consequences of the condition. Epileptic seizures are signs and/or symptoms that appear briefly due to abnormal and synchronous neuronal activity in the brain. This study aims to determine the correlation between the frequency of epileptic seizures with the quality of life in epileptic patients at the Mangusada Hospital. This research is an analytic observational study with a cross sectional research design and uses a consecutive sampling technique. The subjects of this study were 52 epileptic patients who came to the neurosurgery polyclinic at RSUD Mangusada in the period of December 2021 to February 2022. The data were collected by questionnaires, collecting secondary data from patient medical records, and interviews. This research was conducted for 3 months, from December 2021 to Febuary 2022. Data were analyzed by Spearman test. The level of significance in this study obtained results (p) <0.001 which means it has a significant correlation between frequency of epileptic seizures with quality of life. The value (r) in this study is -0.705, the correlation is strong with a negative direction, meaning that the more frequent epileptic seizures occur, the lower the quality of life in epileptic patiens.